A novel fault location method for hybrid lines based on traveling wave. (October 2022) - Xie, Liwei; Luo, Longfu; Ma, Junjie; Li, Yong; Zhang, Mingmin; Zeng, Xiangjun; Cao, Yijia
Highlights: A node ratio coefficient value is given based on the amplitude refraction characteristic of traveling wave at junction nodes. Proposed a novel fault line section identification method via the node ratio coefficient value of junction and fault points. Proposed a revised fault location algorithm to eliminate location errors owing to the variable TW velocity for hybrid lines. The extreme-point symmetric mode decomposition and TEO method is proposed to extract the traveling wave front signals. Abstract: In this paper, a novel fault traveling wave-based location method for hybrid lines is proposed. According to the refraction characteristics of fault traveling wave (TW) at junction nodes, the node ratio coefficient value Q is defined based on the amplitude of traveling wave. Then, by comparing the Q values of junction nodes and fault points, a fault section identification principle is proposed to determine the fault line section for hybrid lines. After identification of fault line section, a double-ended fault location method is revised via adding the location compensation factors to mitigate the effect of traveling wave velocity changes on fault location for multi-section hybrid lines. Additionally, considering the detection problems of arrival time for TW signals, the extreme-point symmetric mode decomposition (ESMD) method and Teager energy operator (TEO) are proposed. The ESMD method is applied to decompose the sampled fault traveling wave signals into several intrinsic modes to filter out the fundamental frequency and low frequency signals. The TEO is employed to track the characteristics of TW signals. Effectiveness of the proposed method is validated in PSCAD. Results show that the ESMD-TEO can detect TW signals effectively, and the proposed fault location method can determine the fault line section and locate fault positions correctly.